2024
DOI: 10.1021/acs.biomac.3c01235
|View full text |Cite
|
Sign up to set email alerts
|

pH and ROS Responsiveness of Polymersome Nanovaccines for Antigen and Adjuvant Codelivery: An In Vitro and In Vivo Comparison

Eliézer Jäger,
Olga Ilina,
Yusuf Dölen
et al.

Abstract: The antitumor immunity can be enhanced through the synchronized codelivery of antigens and immunostimulatory adjuvants to antigen-presenting cells, particularly dendritic cells (DCs), using nanovaccines (NVs). To study the influence of intracellular vaccine cargo release kinetics on the T cell activating capacities of DCs, we compared stimuli-responsive to nonresponsive polymersome NVs. To do so, we employed "AND gate" multiresponsive (MR) amphiphilic block copolymers that decompose only in response to the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, in vitro T cell suppression assays showed that rapamycin-loaded NPs exhibited similar or even better inhibitory performance to CD4 + and CD8 + cells than free rapamycin at different rapamycin concentrations (Figure c). This NP matrix degradation-determined release raises our possibility to precisely control the therapeutic window of drugs, and this stability against environmental influences can reduce premature release and enhance the in vivo performance of NPs . In another case, Little et al demonstrated that a MP system, which slowly releases a T reg -recruiting chemokine in a linear fashion, prevented rejection and promoted hindlimb allograft survival (>200 days) in a rat model …”
Section: Design Of Functional Particles For T Cell-based Immunomodula...mentioning
confidence: 99%
“…Moreover, in vitro T cell suppression assays showed that rapamycin-loaded NPs exhibited similar or even better inhibitory performance to CD4 + and CD8 + cells than free rapamycin at different rapamycin concentrations (Figure c). This NP matrix degradation-determined release raises our possibility to precisely control the therapeutic window of drugs, and this stability against environmental influences can reduce premature release and enhance the in vivo performance of NPs . In another case, Little et al demonstrated that a MP system, which slowly releases a T reg -recruiting chemokine in a linear fashion, prevented rejection and promoted hindlimb allograft survival (>200 days) in a rat model …”
Section: Design Of Functional Particles For T Cell-based Immunomodula...mentioning
confidence: 99%